Comprehensive Guide to Post-Traumatic Stress Disorder 2015
DOI: 10.1007/978-3-319-08613-2_122-1
|View full text |Cite
|
Sign up to set email alerts
|

Case Study of Cognitive Behavioral Therapy for Comorbid PTSD, Insomnia, and Nightmares

Abstract: Sleep disturbances frequently occur concurrently with symptoms of posttraumatic stress disorder (PTSD) and often persist even after successful treatment of PTSD symptoms. This chapter describes the successful treatment of symptoms related to posttraumatic stress disorder and insomnia in a male survivor of military sexual trauma. This individual completed 12 sessions of cognitive processing therapy for PTSD, cognitive only version (CPT-C), followed by four sessions of a cognitive behavioral therapy for nightmar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…For example, there is a protocol, exposure, relaxation, and rescripting therapy (ERRT; Davis & Wright, 2006, 2007) in which IR and IE are combined. Pruiksma et al (2015) tested the ERRT treatment protocol and found it to be effective at reducing nightmare frequency and distress with or without the rescripting and exposure elements. In another study (Lancee, 2010) in which patients simply kept a nightmare diary, they showed significant improvements compared with no treatment.…”
Section: Nightmare Treatments: Variably Effective Underutilized and N...mentioning
confidence: 99%
“…For example, there is a protocol, exposure, relaxation, and rescripting therapy (ERRT; Davis & Wright, 2006, 2007) in which IR and IE are combined. Pruiksma et al (2015) tested the ERRT treatment protocol and found it to be effective at reducing nightmare frequency and distress with or without the rescripting and exposure elements. In another study (Lancee, 2010) in which patients simply kept a nightmare diary, they showed significant improvements compared with no treatment.…”
Section: Nightmare Treatments: Variably Effective Underutilized and N...mentioning
confidence: 99%
“…One randomized controlled trial offering sleep‐directed hypnosis before cognitive processing therapy for PTSD yielded promising results (Galovski et al., ). In one case study, authors reported successful treatment of one patient with PTSD and nightmares using cognitive processing therapy followed by exposure, relaxation, and rescripting therapy (ERRT), which is an empirically based, trauma‐focused intervention for nightmares that shares some similarities with IRT (e.g., nightmare rescripting; Pruiksma, Molino, Taylor, Resick & Peterson, ). Finally, authors of two case studies have described the feasibility and efficacy of combining IRT with CBT for PTSD and offering the two treatments in either order (Levrier, Marchand, Billette, Guay & Belleville, accepted for publication).…”
mentioning
confidence: 99%
“…Selon deux études, l’ERRT, un traitement similaire à la RRIM, mais pour lequel une attention particulière est accordée à l’exposition aux cauchemars et aux souvenirs traumatiques, et la combinaison ERRT et thérapie cognitive (CPT), auraient des effets bénéfiques sur les SPN, c’est-à-dire une diminution des symptômes d’insomnie et de la fréquence des cauchemars (Davis & Wright, 2005; Pruiksma et al, 2015). Cependant, seules ces deux études (une série d’étude de cas et une ERC) ont été effectuées et leur qualité méthodologique n’était pas jugée adéquate selon les critères du Cochrane Back Review Group (Furlan et al, 2009).…”
Section: Synthèse Des Résultatsunclassified